Patterns of use of heparins in ACS - Klein, Werner; Kraxner, Wilfried; Hödl, Ronald; Gabriel Steg, Philippe; Budaj, Andrzej; Gulba, Dietrich; Sadiq, Immad; Van de Werf, Frans; White, Kami; Fox, Keith A.A.; for the GRACE Investigators (Thrombosis and Haemostasis, 2003)
A systematic study that compares the patterns of use of unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) in patients with acute coronary syndromes (ACS) has, to date, not been carried out in the “real-world” setting. The aim of this report is to identify patterns of use of UFH and LMWH and to report their correlates and outcomes in a broad spectrum of ACS patients enrolled in the observational Global Registry of Acute Coronary Events (GRACE).The use of LMWH and UFH was analysed in 13,231 ACS patients according to patient history, concomitant treatment and invasive procedures in US and non-US sites. Frequency of use in hospitals with and without facilities for percutaneous coronary interventions (PCI) was investigated, and outcomes were analysed.Results show that younger patients (<60 years), those receiving antiplatelet therapies, thrombolytics, beta-blockers, angiotensin-converting enzyme inhibitors, patients admitted to hospitals with PCI facilities, and patients undergoing invasive procedures were more likely to receive UFH, or both UFH and LMWH than LMWH alone (80.1% enoxaparin, 19.9% other LMWH). LMWH was used less often in US than non-US sites. After adjusting for confounding variables, patients receiving LMWH had significantly lower rates of hospital mortality (P=0.009) and major bleeding (P<0.0001). Similar results were observed in patients with ST-segment elevation myocardial infarction and non-ST-segment elevation myocardial infarction or unstable angina.We can conclude that UFH tends to be used more frequently than LMWH, but hospital outcomes appeared to be better with LMWH after adjusting for covariables.
Keywords: Low-molecular-weight heparin; unfractionated heparin; acute coronary syndromes; outcomes